2014
DOI: 10.1186/1471-2164-15-743
|View full text |Cite
|
Sign up to set email alerts
|

The I2 resistance gene homologues in Solanum have complex evolutionary patterns and are targeted by miRNAs

Abstract: BackgroundSeveral resistance traits, including the I2 resistance against tomato fusarium wilt, were mapped to the long arm of chromosome 11 of Solanum. However, the structure and evolution of this locus remain poorly understood.ResultsComparative analysis showed that the structure and evolutionary patterns of the I2 locus vary considerably between potato and tomato. The I2 homologues from different Solanaceae species usually do not have orthologous relationship, due to duplication, deletion and frequent sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 64 publications
(94 reference statements)
0
16
0
1
Order By: Relevance
“…Previous studies revealed that miR6024 acts as a trigger of phasiRNA biogenesis, by targeting the I2 gene in tomato and Rx1 gene in potato. 20 , 65 The length of miR6024 is 22 nucleotides in tomato and potato, but 21 nucleotides in pepper ( Supplementary Table S1 ). Because phasiRNA triggers are typically 22 nucleotides in length, 9 can-miR6024-derived phasiRNA biogenesis might not occur in pepper.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that miR6024 acts as a trigger of phasiRNA biogenesis, by targeting the I2 gene in tomato and Rx1 gene in potato. 20 , 65 The length of miR6024 is 22 nucleotides in tomato and potato, but 21 nucleotides in pepper ( Supplementary Table S1 ). Because phasiRNA triggers are typically 22 nucleotides in length, 9 can-miR6024-derived phasiRNA biogenesis might not occur in pepper.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative analysis revealed that presence/absence (P/A) polymorphism is prevalent between species [ 5 , 9 , 19 , 20 ]. An integrated map of R gene loci for a plant family will be helpful to understand the distribution of P/A polymorphism as well as their evolutionary mechanism, and it is also useful for future mapping and cloning of R genes [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…An integrated map of R gene loci for a plant family will be helpful to understand the distribution of P/A polymorphism as well as their evolutionary mechanism, and it is also useful for future mapping and cloning of R genes [ 3 , 5 ]. R gene family represents the most divergent gene family in plant genome, with considerable copy number variation, P/A polymorphism as well as sequence variation caused by various evolutionary mechanisms [ 5 , 18 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ty-2 is a CC-NBS-LRR (CNL) type of gene belonging to the I-2 like subclass of CNL genes. I2-like genes in tomato and potato show high divergence (Wei et al, 2014) and distinctly segregates in sequence and function from other CNLs (Bentham et al, 2018). The resistance mechanism of this subclass of CNLs is unknown (Kourelis and van der Hoorn, 2018).…”
Section: Ty-2 Resistance Mechanismmentioning
confidence: 99%